A checklist of mammals of Gaurishankar Conservation Area, Nepal - Chetri, Madhu; Regmi, Pramod Raj; Dahal, Tulasi Prasad; Thami, Shankar (Nepalese Journal of Zoology, 2022)
Understanding the mammalian fauna is one of the first steps for protected areas management. Proper taxonomic identification is essential for initiating long-term conservation management and species action plans. Here, we present the checklist of mammals of Gaurishankar Conservation Area based on direct observation, field reports, key interviews, focal group discussion, and a literature review. Seventy-seven species of mammals belonging to eight orders and 26 families were known to occur in the region. Of these, only 32 species were of confirmed occurrence and are based on direct observation and camera trap records. The remaining 45 species listed in the checklist were based on interviews and literature. Small mammals of orders Chiroptera and Rodentia were reported less based on interviews and literature surveys, hence needs further studies to confirm their existence. The highest species belonged to the order Carnivora (25 species), followed by Chiroptera (21 species), Rodentia (12 species), Cetartiodactyla (7), Lagomorpha (5), Eulipotyphla (3), Primates (3) and Pholidota (1). A more robust taxonomic study particularly focusing on small mammals is warranted considering the ecological gradients and topography in the region.